Gestión de Riesgos en Proyectos de Construcción Ejecutados mediante Convenios Interinstitucionales Caso de estudio: Asfaltado de los barrios de sur de Tena - Escobar Guzmán, Cecilia Brigith (2024)
Risk management has become a topic of social interest due to the impact generated by risks in construction projects, which directly influence the project's schedule and cost objectives. The objective of this work was to determine risk management in construction projects executed through inter-institutional agreements. Case Study: Asphalting of the southern neighborhoods of Tena. To achieve this objective, the identification of risks, qualitative and quantitative analysis of the risks through a probability and impact matrix, the representation of the “S” curve according to the impact of the risks with respect to the project schedule and cost, and the formulation of a response plan to the identified risks were carried out. The results of our research show that 25% of the identified risks are of high severity, 31.25% of moderate severity and 43.75% of low severity, according to the analysis made of the probability and impact matrix of the risks, and through the “S” curve it is evident that the executed progress of the project is 44.79% for the fourth month while the programmed is 83.20%, which reflects the non-compliance with the schedule, compared to the executed economic progress of the project of US$ 568,792.03 for the fourth month while the programmed amount is $1,080,421.33 dollars, which reflects the non-compliance with the cost.